Effects of Carbon Tax on Electricity Price Volatility: Empirical Evidences from the Australian Market - Nicola Comincioli; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2020)
Among the wide variety of policy options adopted worldwide to control carbon emissions, one of the most environmentally effective and economically efficient is represented by carbon tax, that aims to recoup the damage arising from polluting production processes. In this paper, we focus on the Australian Carbon Pricing Mechanism (CPM) and on the effects that its introduction had on the electricity market. The most relevant effect is the reduction of the level of electricity price's volatility. This effect has been investigated after having removed, from electricity data time series, the periodic behavior, through a multiple linear regression. Then, to study volatility dynamics, we fit a two-states Markov-switching model to represent a high-volatility and a low-volatility states of the world. This model highlighted that in both states the level of volatility is lower and that the persistence of the second state is increased by the presence of the CPM. This result is particularly important in investment evaluation: knowing the different dynamics of price volatility in presence of a carbon tax or not, can provide crucial information in investment decision and its timing.
Keywords: C51; Q41; Q48; 330; Carbon Tax; Seasonality and Volatility of Electricity Price